Comparison of different dietary levels of iron and zinc for the enrichment of eggs in laying hens - Zooheb Ullah; Sarzamin Khan; Muhammad Shuaib; Obaid Ullah; Shahrood Ahmed Siddiqui; Anthony Pokoo-Aikins; Majid S. Jabir; Ayman A. Swelum (Veterinary Quarterly)
Zinc (Zn) and iron (Fe) are necessary for structural and metabolic functions of the body like, immune competence, physical growth, reproductive function, and neurobehavioral development. The deficiency of micronutrients is a severe public health distress in nearly all developing countries which leads to the syndrome of malnutrition mostly in children and women. The present study was conducted to compare the effect of different levels of Fe and Zn on feed intake (FI), feed conversion ratio (FCR), daily egg production, and Fe and Zn depositions in the egg yolk of laying hens. For this purpose, 80 commercial laying birds were allocated into four groups consisting of four replicates each (n = 5). The basal ration was provided to the control group (C) while three different levels (100, 200, and 300 mg/kg diet/element) of Fe and Zn (1:1) were provided to the FZ100, FZ200, and FZ300 groups, respectively. Overall FI, hen day egg production, and FCR were not affected (p > 0.05). The Fe and Zn content in egg yolk were significantly increased in the FZ300 group after 4 weeks of supplementation. The cost per egg produced in response to different levels of Fe and Zn supplementation was not affected however a numerical increase in cost/egg was found in the FZ300 group. In conclusion, Fe and Zn supplementation (300 mg/kg diet/element) significantly enhanced the egg Fe and Zn contents without adversely affecting production parameters including FI, egg production, and FCR of laying hens.